Policy learning and policy networks in theory and practice: the role of policy brokers in the Indonesian biodiesel policy network. Issue 2 (3rd April 2017) - Howlett, Michael; Mukherjee, Ishani; Koppenjan, Joop
Abstract: This paper examines how learning has been treated, generally, in policy network theories and what questions have been posed, and answered, about this phenomenon to date. We examine to what extent network characteristics and especially the presence of various types of brokers impede or facilitate policy learning. Next, a case study of the policy network surrounding the sustainability of palm oil biodiesel in Indonesia over the past two decades is presented using social network analysis. This case study focuses on sustainability-oriented policy learning in the Indonesian biodiesel governance network and illustrates how network features and especially forms of brokerage influence learning.